PENERAPAN MODEL LEARNING TOGETHER (LT) BERBASIS ENTREPRENEURSHIP TERHADAP MINAT WIRAUSAHA DAN HASIL BELAJAR SISWA - Dewi Ularrasyidi Katamsih; Citra Ayu Dewi; Pahriah Pahriah (Universitas Pendidikan Mandalika Mataram, 2016)
Petroleum has characteristics macroscopic, microscopic, and symbolic. All three of these characteristics are related to each other, so that the students in the learning process was difficult to understand the material of petroleum, which leads to lower interest entrepreneurial students and student learning achievement. This problem can be solved by applying the LTmodel based Entrepreneurship. This study aimed to determine the effect of the application of LT models based entrepreneurship to entrepreneurs interests and student learning achievement. This type of research was quasi-experimental research design pretest-posttest control group design. The sample in this study was 70 students of class X SMAN 7 Mataram where was divided into an experimental group of 36 students and a control group of 34 students. The experimental class were learning by LT models based entrepreneurship and control class were learningby conventional learning models. Instruments used include syllabi, lesson plans, worksheets, implementation sheets of lesson plans, interest entrepreneurship test and learning achievement. Data analysis technique using One-Way ANOVA using SPSS 16.0 for Windows. From the results of this study concluded that: (1) Score average interest entrepreneurial students in the experimental class has risen from 71 to 73 who are at high category, and the average score in the control group were also at the high category, but experience changing interests of entrepreneurs from the average score of 71 to 70. (2) the application of LT models based entrepreneurship effect on student learning achievement. This was evidenced by sig. amounting to 0.036> 0.05.